A COMPARATIVE STUDY THE EFFECTIVENEESS OF SHOPEE AND TOKOPEDIA INSTAGRAM SOCIAL MEDIA BY USING THE EPIC MODEL (A CASE STUDY AT THE COLLEGE STUDENT IN BENGKALIS) - Citra Ashira Forkan; Mohammad Alkadri Perdana; Nageeta Tara Rosa (Politeknik Negeri Bengkalis, 2022)
An advertisement can be said to be effective if the objectives of the advertisement can be achieved or not. The purpose of this study was to determine the difference between the effectiveness of Instagram ads on Shopee and the effectiveness of Instagram ads on Tokopedia. The type of research used in this study is a quantitative method with questionnaire data collection techniques. The research was conducted on Bengkalis district students which included State Polytechnic of Bengkalis, STAIN, and STIE who were still active in the 2020/2021 academic year as many as 100 respondents. The variables studied to measure effectiveness were empathy, persuasion, impact, communication including testing the validity and reliability test instruments and the EPIC scale as a measurement scale. The research method used is survey research with data description analysis to test differences in the effectiveness of Instagram ads. By calculating the EPICrate of respondents' opinions on statements that measure each dimension, we get a value of 3.9 for Shopee's EPICrate and 3.5 for Tokopedia. Based on these calculations, it shows that the effectiveness of Shopee's Instagram ads has a higher level of effective scale than Tokopedia's E-Commerce. Thus, Shopee Instagram ads are more effective in attracting consumers than Tokopedia Instagram ads.